Cosmic muon tomography at the Wylfa reactor site utilising an anti-neutrino detector. (27th February 2023) - Bridges, K.; Coleman, J.; Collins, R.; Dasari, J.; Holt, G.; Metelko, C.; Morgan, A.; Murdoch, M.; Schnellbach, Y.; Tsurin, I.; Mills, R.W.; Ryan, M.; et al.
Abstract: An anti-neutrino detector (a prototype of VIDARR) was deployed at the Wylfa Magnox nuclear power station between 2014 and 2016. It was comprised of extruded plastic scintillating bars measuring 4 cm by 1 cm by 152 cm and utilised wavelength shifting fibres (WLS) and Multi-Pixel Photon Counters (MPPCs) to detect and quantify radiation. During deployment, the detector recorded cosmic muon events in accidental coincidence along with the anti-neutrino events. The cosmic muons produced in the upper atmosphere had their paths obscured by the power plant buildings as the cosmic muons originated behind the buildings. Cosmic muons have a significantly higher probability to be attenuated and/or absorbed by denser objects and so one-sided muographic methods were utilised to image the reactor site buildings. In order to achieve clear building outlines a control data set was taken at the University of Liverpool from 2016 to 2018 which had minimal occlusion of the cosmic muon flux by dense objects. By taking the ratio of these two data sets and using GEANT4 simulations it is possible to perform a one-sided cosmic muon tomography analysis. This analysis can be used to discern specific buildings, building heights, and features at the Wylfa reactor site including the reactor core/reactor core shielding using cosmic-ray events equivalent to that which would be seen in ∼ 3 hours of normal operation. This result demonstrates the feasibility of using cosmic muon analysis to determine a segmented detector's location with respect to surrounding buildings, assisted by aerial photography or satellite imagery.